A high‐calcium diet failed to rescue an osteopenia phenotype in claudin‐18 knockout mice. Issue 1 (13th January 2014) - Alshbool, Fatima Z.; Alarcon, Catrina; Wergedal, Jon; Mohan, Subburaman
Abstract We have recently demonstrated that mice with disruption of claudin‐18 (Cldn‐18) gene exhibited osteopenia due to increased bone resorption (BR). In this study, we found that gastric pH was significantly higher in Cldn‐18 knockout (KO) mice compared to heterozygous control mice at 10 weeks of age. To test the possibility that the increased BR in the Cldn‐18 KO mice fed a normal‐Ca diet is a consequence of decreased Ca absorption caused by increased stomach pH, we subjected KO and control mice to a normal‐Ca and high‐Ca diet at birth. Serum Ca levels were significantly lower in Cldn‐18 KO mice compared to control mice at a normal‐Ca diet but not at high‐Ca diet. Dual energy X‐ray absorptiometry revealed that a high‐Ca diet significantly increased lumbar bone mineral density (BMD), but had no effect on femur/tibia BMD in both Cldn‐18 KO and control mice compared to a normal‐Ca diet. While a high‐Ca diet did not affect volumetric BMD, trabecular, and cortical parameters of the lumbar vertebra (LV) as measured by μCT, the size of the LV did increase, in both genotypes due to reduced BR. Comparison of the skeletal phenotype of high‐Ca Cldn‐18 KO and control mice revealed that an osteopenia phenotype seen at a normal‐Ca diet was still maintained at different skeletal sites in the KO mice till 10 weeks of age. In conclusion, our findings suggest that increased BR is likely caused by direct effects of a lack of Cldn‐18 on osteoclasts rather than gastric pH changes.